2015
DOI: 10.1002/ijc.29531
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nuclear matrix proteins binding matrix attachment regions in prostate cancer. PARP‐1: New player in tumor progression

Abstract: Prostate cancer (PCa) displays infrequent point mutations, whereas genomic rearrangements are highly prevalent. In eukaryotes, the genome is compartmentalized into chromatin loop domains by the attachment to the nuclear matrix (NM), and it has been demonstrated that several recombination hot spots are situated at the base of loops. Here, we have characterized the binding between NM proteins and matrix attachment regions (MARs) in PCa. Nontumor and 44 PCa tissues were analyzed. More aggressive tumors were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…In considering the multifaceted role of PARP-1, it is worth mentioning that many reports showed increased levels of PARP-1 or, more generally, pointed to PARP-1 involvement in carcinogenesis, as for instance is the case for primary prostatic cancer [61]. PARP-1 has also been involved in prostate cancer progression, as PARP-1 expression in the nuclear matrix increases with tumor invasiveness [62]. Finally, both enzymatic activity and transcriptional regulatory functions of PARP-1 were reported to be elevated as a function of prostate cancer progression, independently of DNA double strand breaks, but through enhancement of E2F1-mediated induction of DNA repair factors involved in HR [63].…”
Section: High Activity Of Parp-1 In Tumor Development and Progressionmentioning
confidence: 99%
“…In considering the multifaceted role of PARP-1, it is worth mentioning that many reports showed increased levels of PARP-1 or, more generally, pointed to PARP-1 involvement in carcinogenesis, as for instance is the case for primary prostatic cancer [61]. PARP-1 has also been involved in prostate cancer progression, as PARP-1 expression in the nuclear matrix increases with tumor invasiveness [62]. Finally, both enzymatic activity and transcriptional regulatory functions of PARP-1 were reported to be elevated as a function of prostate cancer progression, independently of DNA double strand breaks, but through enhancement of E2F1-mediated induction of DNA repair factors involved in HR [63].…”
Section: High Activity Of Parp-1 In Tumor Development and Progressionmentioning
confidence: 99%
“…To this aim, we generated DNA damage on a selected subregion of the nuclei by 405 nm‐laser microirradiation and sensitization with Hoechst 33342, as reported previously . To verify that 405 nm‐laser microirradiation generated local DNA damage in HeLa cell nuclei stained with Hoechst 33342, employed as a sensitizer, we monitored the expression of the DDR marker PARP‐1, a specific protein that rapidly accumulates at genome sites where single‐strand breaks or DSBs have occurred . The expression of PARP‐1 was monitored in cells fixed immediately after microirradiation and in live cells (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Expression levels do not vary significantly in prostate cancers but there are some evident changes observed in context with PARP protein in the nuclear matrix and matrix attachment regions in prostate cancers. PARP1 expression in the nuclear matrix increases with tumor aggressiveness . Transcriptional regulation of some nuclear hormone receptors involves PARP1 and hence PARP could regulate AR target genes.…”
Section: Functional Role Of Parp1 In Various Cancersmentioning
confidence: 99%
“…PARP1 expression in the nuclear matrix increases with tumor aggressiveness. 65 Transcriptional regulation of some nuclear hormone receptors involves PARP1 and hence PARP could regulate AR target genes. Wang et al have reported a decrease in the AR recruitment to promoters of its target genes in presence of PARPi.…”
Section: Parp1 In Prostate Cancermentioning
confidence: 99%